A Small-angle Neutron-scattering Study in Fe-Pt-Al - Thang, Pham Duc (Communications in Physics, 2011)
In this paper a study on small-angle neutron-scattering (SANS) of the Fe-Pt-Al alloys was presented. The scattering intensities in an external magnetic field of 1.2 T, perpendicular to the neutron-beam direction, are significantly smaller than these in the initial state. The experimental data were analyzed by means of the monodisperse and polydisperse models, depending on the sample state. The correlation between the derived results and other microstructure analyses will also be discussed.